The Potential of Utilizing Cattle (Cow) Manure for Biomethane Production—An Experiment for Photofermentation - Anita Konieczna; Kinga Borek; Jakub T. Hołaj-Krzak; Barbara Dybek; Dorota Anders; Jan Szymenderski; Kamila Klimek; Magdalena Kapłan; Zbigniew Jarosz; Serhiy Syrotyuk; Taras Stanytskyy; Serhii Korobka; et al. (Energies, 2024)
This article presents the current state of biogas (biomethane) production technology with an example of using cow manure from the perspective of photofermentation efficiency. In specialist farms, there is a problem of waste management in the form of manure; analyses were carried out on the photocatalysis process in order to be able to effectively produce biomethane based on monosubstrate solutions (manure). Cow manure was tested for its elemental composition in order to determine the suitability of this raw material for biogas production. The elemental composition was compared in material A, which was stored for 1 week (fresh sample, wet), and material B, which was stored for 1 month (old sample, dry). In material A and material B, the values were as follows: N: 3.18% and 3.34%; P: 0.403% and 0.492%; K: 1.267% and 2.336%; Na: 0.362% and 0.714%; Ca: 0.705% and 0.788%; and Mg: 0.737% and 0.907%. The quality of biogas produced in atmospheric conditions from cow manure (material A and material B) was assessed. An increase in CH4 production was observed with an increase in temperature. For material A, at a temperature of 22.5 °C, it was in the range of 11–14%; for a temperature of 25.5 °C, it was approx. 35%. For material B, despite small amounts (from 0% to 2%), a tendency to increase CH4 production with an increase in temperature was also observed. At 22.4 °C, it was in the range of 0–1%, and at 25.4 °C, it was about 2%. The novelty of this article is the development of an innovative method of using cow manure, indicating the development of the biomethane industry.